Inventory on the bird communities present in Cataisan Point, San Jose, Tacloban City. - Molina, Sheena Aira E.; Casas, Eulito Jr. V. (Sheena Aira E. Molina, 2018)
Mangrove ecosystem plays a vital role for the coastal organisms such as birds, for which they are closely associated. Studies reported that mangrove ecosystems play a significant role in conservation of not only resident species but also migratory birds. In this study, bird species inventory was conducted along the coastal area of Cataisan Point, San Jose, Tacloban City. Three station points were established on the vicinity of the mangrove forest. A 20-minute survey in each station point was conducted. Observations were recorded using bulls-eye and standardized frequency data sheets. To supplement the identification of bird species, a spotting scope with a camera attached to its eyepiece was used. A bird expert identified and confirmed the bird species observed. There was a total of 641 individuals from 23 different species of birds belonging to 17 families which 7 endemic, 9 resident and 7 migratory bird species were observed during the conduct of the study. The endemic species observed are Anaz luzonica, Aerodramus mearnsi, Collocalia troglodytes, Centropus viridis, Rhipidura. nigritorquis, Ninox. philippensis and Hypsipetes philippinus. A number of migratory birds were also recorded in the site: Egretta garzetta, Ardea cinerea, Artamus leucorynchus, Lanius cristatus, Passer montanus, Numenius phaeopus and Actitis hypoleucos. The most abundant bird species found in all station points was Collocalia troglodytes, followed by Lonchura atricapilla, both bird species are considered as common and highly adapted to human settlements in urban areas. Cataisan Point proved to be a suitable habitat to bird species among other wildlife. Considering the amount of transformation and degradation that has occurred in the study area due to typhoons, the presence of these diverse assemblage of birds serves as an indicator that mangroves of Cataisan have recovered and provide suitable environment to several bird species.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.